The modulation of various signal transduction pathways in colorectal carcinoma cells by docosahexaenoic acid - Du Toit, Joe-Lin (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2006.